Bringing injustice back in: Secondary victimization as epistemic injustice - Pemberton, Antony (Criminology & criminal justice, 2025)
Secondary victimization is a key concept in research into the experiences of victims of crime, related policies and legislation, and practices of support and care. However, the current conceptualization of secondary victimization suffers from a number of shortcomings. These include conceptual confusion, such that negative but varied emotional and psychological experiences are lumped together. Moreover, the current conceptualization of secondary victimization is too narrow, in that it tends to neglect the absence of actions and more covert structural biases of the criminal justice system, and too broad, in that it makes no distinction between voluntary and involuntary modes of victim participation. We argue that these shortcomings can be overcome by articulating the injustice in secondary victimization by reference to Miranda Fricker’s notion of epistemic injustice. Secondary victimization wrongs victims in their capacity as knowers. To develop this idea, the article highlights the connections between the literature on epistemic injustice and victimology.